Optimizing the Management and Empowerment of Professional Zakat in Realizing Community Welfare in Indonesia Jambi City - Tiara Zhalpa (Dinasti International Journal of Management Science, 2022)
The purpose of this study is to find out how the management, distribution and utilization of professional zakat in the welfare of the community in Jambi City. The method in this study uses a descriptive qualitative approach, where data is collected using interviews, observation and documentation techniques. . Based on the results of researchers in the field that the management of the Jambi City Baznas is maximal and in accordance with the principles of zakat management that have been put forward by Yusuf Qardawi, one of which is that the management of zakat in the Jambi City Baznas is more transparent and open, both in the distribution, utilization and financial fields. very open because we can all see it or access it both from social media and in various counseling held by the Jambi City Baznas. However, the management division in the field of supervision at the Jambi City Baznas is not yet optimal because in terms of its own supervision, the Jambi City Baznas is still lacking. From the results of research analysis, for the distribution mechanism of professional zakat funds in the Jambi City Baznas consumptively, namely by providing assistance in the form of money to mustahiq, while assistance in the form of productive assistance is given in the form of what is needed by mustahiq in the form of money, storefronts, sewing machines, agricultural and livestock seeds. The assistance prioritized by the Jambi City Baznas is assistance in the form of consumptive rather than productive ones. And priority assistance is given to the needy and poor. Based on the results of research analysis in the field of zakat utilization at the Jambi City Baznas, it has not fully run optimally because the utilization of productive zakat distributed to mustahiq uses a grant contract where all assistance that has been given to mustahiq will become their full property so that many mustahiqs have been given assistance. but no longer reports to the Jambi City Baznas how its business is progressing, this is also due to the lack of supervision and assistance from the Baznas itself.